soil microbial community predicts the importance of plant traits in plant–soil feedback - Ke, Po‐Ju; Miki, Takeshi; Ding, Tzung‐Su (The New phytologist, 2015)
Reciprocal interaction between plant and soil (plant–soil feedback, PSF) can determine plant community structure. Understanding which traits control interspecific variation of PSF strength is crucial for plant ecology. Studies have highlighted either plant‐mediated nutrient cycling (litter‐mediated PSF) or plant–microbe interaction (microbial‐mediated PSF) as important PSF mechanisms, each attributing PSF variation to different traits. However, this separation neglects the complex indirect interactions between the two mechanisms. We developed a model coupling litter‐ and microbial‐mediated PSFs to identify the relative importance of traits in controlling PSF strength, and its dependency on the composition of root‐associated microbes (i.e. pathogens and/or mycorrhizal fungi). Results showed that although plant carbon: nitrogen (C : N) ratio and microbial nutrient acquisition traits were consistently important, the importance of litter decomposability varied. Litter decomposability was not a major PSF determinant when pathogens are present. However, its importance increased with the relative abundance of mycorrhizal fungi as nutrient released from the mycorrhizal‐enhanced litter production to the nutrient‐depleted soils result in synergistic increase of soil nutrient and mycorrhizal abundance. Data compiled from empirical studies also supported our predictions. We propose that the importance of litter decomposability depends on the composition of root‐associated microbes. Our results provide new perspectives in plant invasion and trait‐based ecology.